Analisis Rasio Solvabilitas untuk Mengukur Kinerja Keuangan pada PT. Mizuho Leasing Indonesia Tbk Periode 2019-2023 - Annisa Mawaddah; Fitriana Indah Lestari Rambe; Siti Intan Kumala Sari (Al-Manar Journal of Accountancy and Business Studies, 2025)
Solvency ratio analysis is important to assess the financial performance of finance companies, especially the leasing industry that relies on external funds. In the economic conditions of 2019-2023, including the impact of the COVID-19 pandemic, the evaluation of capital structure is increasingly crucial. This study aims to examine the financial performance of PT Mizuho Leasing Indonesia Tbk by using solvency ratio analysis, which includes Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Times Interest Earned Ratio (TIER). The method applied is a descriptive quantitative approach by utilizing secondary data, namely audited annual financial reports for 2019-2023 and sourced from the website www.mizuho-ls.co.id. The results of this study show that the company's DER and DAR are within reasonable limits for the leasing sector, although it still shows a considerable dependence on loans. On the other hand, the TIER ratio shows a very low number during the study period, illustrating that profit before tax has not been able to cover interest expenses well. This finding indicates a financial risk that needs to be managed carefully. In conclusion, the company's financial structure still requires improvement, especially in terms of operational efficiency and debt management, in order to increase the margin of safety and strengthen the confidence of investors and creditors in the sustainability of the company's business.